Gallbladder neuroendocrine carcinoma: A single center experience. Issue 36 (4th September 2020) - Chu, Hongwu; Zhang, Chengwu; Shi, Ying; Wu, Weiding; Hu, Zhiming; Zhang, Jungang; Huang, Dongsheng
Abstract : Abstract: Gallbladder neuroendocrine carcinoma (GB-NEC) is a group of rare and heterogeneous neoplasms and there are few reports at present. We analyzed the clinical and pathological features of 7 patients with GB-NEC who were admitted to Zhejiang Provincial People's Hospital from January 2011 to October 2019. The median age of 7 patients was 58 years with male to female ratio of 1:2.5. Right upper quadrant discomfort was the main complaint and no patients presented carcinoid syndrome-related symptoms. In contrast-enhanced computed tomography (CT) examination, 5 of 6 patients showed well-defined margin and continuous thin line-like contrast enhancement on the mucosa. Among the patients with liver metastases before surgery, 66.7% of patients were cancer antigen 125 (CA-125) positive, and among the patients presented with liver metastases during follow-up period, all patients were CA-125 positive. All patients with elevated CA-125 did not have ascites, ovarian carcinoma, peritoneal carcinoma, and endometrial carcinoma. According to postoperative pathological report, 1 patient was stage IIIA, and the other 6 patients were stage IVB. Six patients underwent surgery, and 1 patient just underwent liver biopsy. Two patients underwent laparoscopic radical cholecystectomy, and neither of them encountered serious complications after surgery with the overall survival time of 4.6 and 16.8 months, respectively. Compared with the patients without chemotherapy, 3 patients postoperatively treated with chemotherapy lived longer. The median survival of all 7 patients was 4.6 months and the 1-, 2-year survival rates were 14.29%, 0%. Surgical resection, including laparoscopic radical cholecystectomy, is feasible for the treatment of advanced GB-NEC in selected patients and has the advantages of prolonging survival in combination with chemotherapy. The elevation of CA-125 can be utilized as an important predictor of poor prognosis, while more investigations are necessary to confirm it.